Identification of Factors Affecting the Enhancement of Practical Course Instruction Quality: A Systematic Review - Nematipour, Leila; Mashinchi, Aliasghar; Hashemi , Seyed Ahmad (Assessment and Practice in Educational Sciences, 2026)
The aim of the present study is to provide a systematic review of the literature related to the enhancement of the quality of practical course instruction, with a focus on identifying the key factors influencing it. The research question addressed in this article is: what are the factors affecting the improvement of the quality of practical course instruction at the secondary education level? The present study is descriptive in nature, applied in terms of purpose, and was conducted using a systematic review methodology. The analysis of theoretical literature was carried out in the Scopus database using keywords such as instructional improvement, course instruction quality, and practical course instruction quality within the time frame from 2000 to the end of 2024, resulting in the selection of 47 articles. The findings indicated that multiple factors—including a positive school climate and school culture, teacher effectiveness, strong leadership, technological resources and digital literacy, the flipped classroom approach, school efficiency, and demographic and social characteristics—play a role in enhancing the quality of practical course instruction at the secondary education level.